1998
DOI: 10.1017/s0890037x00044225
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nitrogen Fertilizer Placement to Weed Management in Spring Wheat (Triticum aestivum)

Abstract: The contribution of nitrogen (N) fertilizer placement to management of annual weeds in spring wheat grown under two tillage systems was examined at sites located in three ecoregions of the northern Great Plains from 1994 to 1996. The effect of three different fertilizer placements on narrowleaf and broadleaf weed emergence, growth, and N uptake were determined in a no-till and a conventional tillage system. Fertilizer was broadcast, subsurface-banded in the spring prior to seeding, or side-banded at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 10 publications
4
76
1
Order By: Relevance
“…However, although foxtail barley biomass and seed yield were unaffected, wheat yield was greater when N was banded than when surface broadcast in both tillage systems in 1996 (Table 4). Previous studies have found that banding compared with surface broadcasting fertiliser often results in greater N use efficiency and higher crop yields (Koehler et al 1987;Janzen et al 1990;Kirkland and Beckie 1998). Wheat protein content was not affected by N placement in 1996.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, although foxtail barley biomass and seed yield were unaffected, wheat yield was greater when N was banded than when surface broadcast in both tillage systems in 1996 (Table 4). Previous studies have found that banding compared with surface broadcasting fertiliser often results in greater N use efficiency and higher crop yields (Koehler et al 1987;Janzen et al 1990;Kirkland and Beckie 1998). Wheat protein content was not affected by N placement in 1996.…”
Section: Resultsmentioning
confidence: 83%
“…Banding compared with broadcasting N on the soil surface can reduce the competitive ability of annual weeds such as downy brome (Rasmussen 1995), green foxtail (O'Donovan et al 1997) and wild oat (Reinertsen et al 1984;Kirkland and Beckie 1998;Thill et al 1994) and increase crop yield. In contrast, other studies reported that N placement had little effect on the competitive ability of downy brome (Cochran et al 1990) or green foxtail (Kirkland and Beckie 1998). Further research is required to determine why differences occurred among studies and to determine the response of other weed species, including perennials, to N placement.…”
mentioning
confidence: 99%
“…For example, Peterson and Nalewaja (1992) found that green foxtail responded more to N fertilization than spring wheat. In contrast, Kirkland and Beckie (1998) found that N fertilization increased spring wheat competitiveness against green foxtail.…”
Section: Soil Nutrient Managementmentioning
confidence: 82%
“…More information regarding crop-weed interactions using current crop production systems and cultivars, weed emergence patterns, and the spatial heterogeneity of weeds is needed to improve the facility and value in using ETs . The competitive ability of crops and weeds depends heavily on environmental conditions, and can vary even for the same crop-weed pair (Peterson and Nalewaja 1992;Kirkland and Beckie 1998). However, ETs generally do not include these considerations but are based on simple weed densities.…”
Section: Economic Thresholds For Weedsmentioning
confidence: 99%
See 1 more Smart Citation